Colorectal polypectomy and endoscopic mucosal resection (EMR): European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline - Ferlitsch, Monika; Moss, Alan; Hassan, Cesare; Bhandari, Pradeep; Dumonceau, Jean-Marc; Paspatis, Gregorios; Jover, Rodrigo; Langner, Cord; Bronzwaer, Maxime; Nalankilli, Kumanan; Fockens, Paul; Hazzan, Rawi; Gralnek, Ian M.; Gschwantler, Michael; Waldmann, Elisabeth; Jeschek, Philip; Penz, Daniela; Heresbach, Denis; Moons, Leon; Lemmers, Arnaud; Paraskeva, Konstantina; Pohl, Juergen; Ponchon, Thierry; Regula, Jaroslaw; Repici, Alessandro; Rutter, Matthew D.; Burgess, Nicholas G.; Bourke, Michael J. (Endoscopy, 2017)
1 ESGE recommends cold snare polypectomy (CSP) as the preferred technique for removal of diminutive polyps (size ≤ 5 mm). This technique has high rates of complete resection, adequate tissue sampling for histology, and low complication rates. (High quality evidence, strong recommendation.)2 ESGE suggests CSP for sessile polyps 6 – 9 mm in size because of its superior safety profile, although evidence comparing efficacy with hot snare polypectomy (HSP) is lacking. (Moderate quality evidence, weak recommendation.)3 ESGE suggests HSP (with or without submucosal injection) for removal of sessile polyps 10 – 19 mm in size. In most cases deep thermal injury is a potential risk and thus submucosal injection prior to HSP should be considered. (Low quality evidence, strong recommendation.) 4 ESGE recommends HSP for pedunculated polyps. To prevent bleeding in pedunculated colorectal polyps with head ≥ 20 mm or a stalk ≥ 10 mm in diameter, ESGE recommends pretreatment of the stalk with injection of dilute adrenaline and/or mechanical hemostasis. (Moderate quality evidence, strong recommendation.)5 ESGE recommends that the goals of endoscopic mucosal resection (EMR) are to achieve a completely snare-resected lesion in the safest minimum number of pieces, with adequate margins and without need for adjunctive ablative techniques. (Low quality evidence; strong recommendation.) 6 ESGE recommends careful lesion assessment prior to EMR to identify features suggestive of poor outcome. Features associated with incomplete resection or recurrence include lesion size > 40 mm, ileocecal valve location, prior failed attempts at resection, and size, morphology, site, and access (SMSA) level 4. (Moderate quality evidence; strong recommendation.)7 For intraprocedural bleeding, ESGE recommends endoscopic coagulation (snare-tip soft coagulation or coagulating forceps) or mechanical therapy, with or without the combined use of dilute adrenaline injection. (Low quality evidence, strong recommendation.)An algorithm of polypectomy recommendations according to shape and size of polyps is given (Fig. 1).